An overview of the pharmacology of olive oil and its active ingredients. (17th August 2019) - Visioli, Francesco; Davalos, Alberto; López de las Hazas, María‐Carmen; Crespo, María Carmen; Tomé‐Carneiro, Joao
Abstract : In addition to providing sensory stimuli, usually taste, smell and sight, olive oil contains a range of minor components, mostly phenolic in nature. These components are endowed with pharmacological or pharma‐nutritional properties that are the subject of active research worldwide. Based on our more than 25 years of experience in this field, we critically focus on what we believe are the most pharmacologically prominent actions of the constituents of olive oil. Most of the effects are due to the phenolic compounds in extra virgin olive oil, such as hydroxytyrosol and oleocanthal (which are often mis‐categorized as in vivo antioxidants) and concern the cardiovascular system. Other potentially beneficial activities are still to be investigated in depth. We conclude that—in the context of a proper diet that includes high‐quality products—the use of high‐quality olive oil contributes to achieving and sustaining overall health. Linked Articles: This article is part of a themed section on The Pharmacology of Nutraceuticals. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v177.6/issuetoc